Desempenho cognitivo de idosos cuidadores e sua relação com o contexto de cuidado - Ottaviani, Ana Carolina (2019)
The task of caring can bring benefits to caregivers, but it can also have negative effects on their physical, psychological and mental health. The general objective of this study was to analyze the cognitive performance of older caregivers and their relationship with the context of care. Three studies were developed: the first was a longitudinal study aimed at comparing cognitive performance and care context variables in 61 older caregivers. Data on sociodemographic characteristics and the context of care, daily life activities, cognition, burden, and depressive symptoms were collected. There was a significant difference between the assessments in the first and second evaluations for: language cognitive domain (p = 0.024), receiving material help (p = 0.020), care time (p = 0.045), and greater dependence on basic activities of daily living of the care recipient (p = 0.042). The second study consisted of a systematic review that aimed to analyze the use of P300 in healthy elderly. We analyzed 26 articles and it was identified that there is increased latency and lower amplitude with increasing age. In addition, it was found that the increase in latency is more pronounced in the elderly with cognitive impairment. The third study had as objective to analyze the factors associated to the cognitive processing of 75 older caregivers considering differences between the age groups. Data on sociodemographic characterization, care, health, cognition and cognitive processing were collected. In the group of 60 to 69 years (n = 43) there were moderate correlations between cognitive processing and variables related to the context of care, health and cognitive domains memory and language. In the group of 70 years and over (n = 32), there was a moderate and strong correlation between cognitive processing and cognition in the attention and orientation domains, memory, verbal fluency, language and visuospatial ability. We concluded that different factors concerning the context of care are related to the cognitive performance of older caregivers of other older people. There is evidence of the need to plan actions with caregivers in primary health care due to the importance of cognition in the outcome of older care and health.